Mobile health applications for postnatal care: Review and analysis of functionalities and technical features. (February 2020) - Sardi, Lamyae; Idri, Ali; Redman, Leanne M.; Alami, Hassan; Bezad, Rachid; Fernández-Alemán, José Luis
Highlights: An analysis of functionalities and technical features of 48 postnatal care mobile applications is provided. Apps for monitoring newborn activities is the focus area mostly predominant among postnatal care apps. The most commonly offered functionalities in the postnatal care apps assessed are inputting newborn's birthday followed by tracking newborn's vital measurements. The technical features evaluated were related to privacy, security, usability and internationalization. Informal writing style and intuitive navigation patterns were the two prevalent features in the postnatal care apps considered. Most of the postnatal care apps assessed overlook mother's health tracking during the postpartum period. Abstract: Background: Providing a continuum of care from antenatal, childbirth and postnatal period results in reduced maternal and neonatal morbidity and mortality. Timely, high quality postnatal care is crucial for maximizing maternal and newborn health. In this vein, the use of postnatal mobile applications constitutes a promising strategy. Methods: A Systematic Literature Review (SLR) protocol was adopted to perform the selection, data extraction and functional evaluation of the available postnatal apps on iOS and Android platforms. The analysis of the functionalities and technical features of the apps selected was performed according to a 37-items assessment questionnaire developed on the basis of the scientific literature of postnatal care and a preliminary analysis of available postnatal apps Results: A total of 48 postnatal apps were retrieved from the app repositories of the iOS and Android platforms. The results of the functional content analysis show that the postnatal apps selected relatively achieved low scores owing to the complexity and the ramification of the postnatal care. Conclusions: The present study helps in identifying areas related to the postnatal care that require further endeavors to be properly addressed. It also provides directions for developers to leverage the advancement and innovation on mobile technology to build complete and well-suited postnatal apps